Monitoring the conversion from brand name to generic mycophenolate mofetil in kidney transplant recipients - Gouveia,Rita (2015)
Generic mycophenolate mofetil (MMF) is a cheaper and possibly equally effective option as the original molecule for maintenance immunosuppression in solid organ transplant recipients. In order to be approved, each generic formulation has to prove bioequivalence to the reference product in healthy volunteers. However, MMF pharmacokinetics may be different between healthy volunteers and transplant recipients. Faced with the introduction of the generic formulation in the pharmacy of their kidney transplant unit, the authors studied and compared the exposure to mycophenolic acid (MPA) before and after the switch in 14 kidney transplant recipients converted to the generic molecule. The exposure to MPA as evaluated by the AUC0-12h estimated by a limited sample strategy was slightly higher with the generic formulation (40.49 versus 34.96mcg.h/mL, p = 0.041). There was no significant variation in the eGFR, haemoglobin and leucocyte count after the switch. Only one of the patients converted to the generic formulation developed de novo adverse gastrointestinal effects, which resolved after restart of the original formulation. In conclusion, in our cohort there was no clinically significant variation in the exposure to MPA, kidney graft function or incidence of adverse events with the generic formulation on a short follow-up period